Analisis biaya aktual pada usaha pendederan udang vaname sistem bioflok skala rumah tangga - Suderajad, Pono; Nur, Indriani; Yusnaini; Rosmawati (Jurnal Sosial Ekonomi Perikanan, 2024)
Household-scale shrimp nursery using a biofloc system is an innovative approach to shrimp cultivation, with great potential to be promoted as a source of additional income for fishing households in coastal areas. However, there is still a need for a deeper study regarding the components and amount of costs incurred in running this business. The main purpose of actual cost analysis is to compare the actual costs incurred with the previously planned cost estimates. This helps businesses understand in detail how their budget is used and identify areas where expenses can be better managed or reduced, thereby determining the selling price of a product. Based on the analysis, there is a difference between the standard purchasing price (HBs) and the actual purchasing price (HBa) which is specific to certain material component items. The price difference calculation is determined to have the characteristic of a profitable price difference because HBa < HBs, so the price difference is said to be profitable. This favorable price difference will be allocated for unexpected costs, such as additional costs for feed, or maintenance costs for equipment and materials used in the household scale biofloc system shrimp nursery business